Effect of Zn2+, Fe3+ and Cr3+ addition to hydroxyapatite for its application as an active constituent of sunscreens - Araujo, Tatiana Santos de (2010)
Biocompatible phosphate materials are used in different applications like bone and dental implants, drug delivery systems and others, but could also be applied in inorganic sunscreens. Using sunscreens is extremely necessary, because long time exposure to sun can cause skin cancer. In this work chemical precipitation method has been used to produce hydroxyapatite. Cr3+, Zn2+ and Fe3+ doped samples were characterized using powder X-Ray Diffraction (XRD) and Optical Absorption techniques. X-ray diffraction measurements confirmed the materials were in the expected crystalline structures. The crystallite size as measured from the X-ray pattern was 23–27 nm (±1).The absorption spectra in the ultraviolet and visible ranges indicate that appropriately doped and sized hydroxyapatite particles may have potential applications as active constituents of sunscreens.